Novel molecules mediate specialized functions of human regulatory macrophages. Issue 5 (October 2018) - Riquelme, Paloma; Hutchinson, James A.
Abstract : Purpose of review: Now that adoptive transfer of regulatory macrophages (Mregs) is clinically practicable, we ask whether this approach could be used to achieve self-sustaining peripheral regulation and what mechanisms may be involved. Recent findings: Dehydrogenase/reductase 9 (DHRS9)-expressing Mregs are a specialized subset of monocyte-derived macrophages that are currently being investigated as a tolerogenic cell-based therapy. Human Mregs are defined by their capacity to convert naïve CD4 + T cells to IL-10-secreting FoxP3 + regulatory T cells (Tregs) through an activation-dependent process involving signals mediated by TGF-β, retinoic acid, indoleamine 2, 3-dioxygenase activity, notch and progestagen associated endometrial protein (PAEP). Mreg-induced iTregs (miTregs) are a phenotypically distinct type of in-vitro-derived human iTreg that expresses butyrophilin-like protein 8 (BTNL8) and T cell immunoreceptor with Ig and ITIM domains (TIGIT). miTregs are nonspecifically suppressive of mitogen-stimulated bystander T cell proliferation and inhibit TNFα-induced maturation of monocyte-derived dendritic cells. Preclinical and clinical studies find that intravenous infusion of allogeneic Mregs leads to enrichment of circulating TIGIT + Tregs. Summary: These results suggest a feed-forward mechanism by which Mreg treatment could promote solid organ transplant acceptance through rapid induction of direct pathway Tregs.